Relationship between omentin-1 and carotid intima thickness in type 2 diabetes mellitus - Hend M Tawfeek; Hala M Maghrapy; Fadila M Elsaid; Hanaa Abou Eliazeed (SpringerOpen, 2014)
Introduction Omentin-1 is a novel adipokine that has a pivotal role in modulating insulin sensitivity, immunity, and inflammation. Adipokines contribute directly to the atherosclerotic process. The current study was conducted to evaluate the serum omentin-1 level in type 2 diabetes mellitus (DM) patients and to evaluate its relationship with carotid intima media thickness (CIMT). Patients and methods Sixty participants were enrolled in the study: 30 patients with type 2 DM and 30 controls with normal glucose levels. Patients were classified into group I, which included 15 patients with CIMT greater than 0.9 mm, and group II, including 15 patients with CIMT less than 0.9 mm. All groups were subjected to full medical history taking, clinical examination, and assessment of fasting blood glucose levels, lipid profile, and serum omentin-1 levels using enzyme-linked immunosorbent assay. BMI and CIMT were also assessed using color Doppler ultrasound. Results Serum omentin-1 levels were significantly decreased in patients with type 2 DM compared with controls and were further decreased in patients with increased CIMT. Omentin-1 levels were negatively correlated with fasting blood sugar, BMI, waist circumference, lipid profile, and CIMT, and were positively correlated with high-density lipoprotein, with r-values of −0.72, −0.9, and −0.81 for fetal bovine serum, BMI, and CIMT, respectively; −0.58, −0.70, and −0.49 for triglyceride, low-density lipoprotein, and cholesterol, respectively; and +0.66 for high-density lipoprotein. Conclusion Serum omentin-1 level is decreased in type 2 DM patients and is negatively correlated with CIMT and BMI. Hence, omentin-1 could serve as a protective marker and predictor for cardiovascular disease. Further study needed to show whether omentin-1 is considered as a risk factor for DM.